Развитие и выживаемость зародышей стронгилят овец и крупного рогатого скота и сезонная динамика численности популяций этих гельминтов в Степи УССР - Трач, В.Н. (Вестник зоологии, 1970)
From June 3, 1963 to July 30, 1967 at the pastures in the Ukrainian Steppe the experiments were carried out for studying the periods of development and survival rate of eggs and larvae of Strongylata in excrements of sheep and cattle of different age. The duration of development and life time are established of larvae of the III stage, parasitizing in sheep and cattle. In excrements of animals at the age of one year and younger the maximum quantity of Strongylata larvae was registered in September — October, more seldom in November and in the excrements of animals older than one year in March —May and August — October. Seasonal changes in the quantity of Strongylata populations are considered by the author as seasonal adaptations of these helminths.